Fibrotic Aortic Valve Stenosis in Hypercholesterolemic/Hypertensive Mice. Issue 3 (March 2016) - Chu, Yi; Lund, Donald D.; Doshi, Hardik; Keen, Henry L.; Knudtson, Kevin L.; Funk, Nathan D.; Shao, Jian Q.; Cheng, Justine; Hajj, Georges P.; Zimmerman, Kathy A.; Davis, Melissa K.; Brooks, Robert M.; et al.
Abstract : Objective—: Hypercholesterolemia and hypertension are associated with aortic valve stenosis (AVS) in humans. We have examined aortic valve function, structure, and gene expression in hypercholesterolemic/hypertensive mice. Approach and Results—: Control, hypertensive, hypercholesterolemic ( Apoe −/− ), and hypercholesterolemic/hypertensive mice were studied. Severe aortic stenosis (echocardiography) occurred only in hypercholesterolemic/hypertensive mice. There was minimal calcification of the aortic valve. Several structural changes were identified at the base of the valve. The intercusp raphe (or seam between leaflets) was longer in hypercholesterolemic/hypertensive mice than in other mice, and collagen fibers at the base of the leaflets were reoriented to form a mesh. In hypercholesterolemic/hypertensive mice, the cusps were asymmetrical, which may contribute to changes that produce AVS. RNA sequencing was used to identify molecular targets during the developmental phase of stenosis. Genes related to the structure of the valve were identified, which differentially expressed before fibrotic AVS developed. Both RNA and protein of a profibrotic molecule, plasminogen activator inhibitor 1, were increased greatly in hypercholesterolemic/hypertensive mice. Conclusions—: Hypercholesterolemic/hypertensive mice are the first model of fibrotic AVS. Hypercholesterolemic/hypertensive mice develop severe AVS in the absence of significant calcification, a feature that resembles AVS in children and some adults. Structural changes at the base of the valve leaflets include lengthening of the raphe, remodeling of collagen, and asymmetry of the leaflets. Genes were identified that may contribute to the development of fibrotic AVS. Abstract : Supplemental Digital Content is available in the text.